1987
DOI: 10.1152/ajpregu.1987.253.6.r942
|View full text |Cite
|
Sign up to set email alerts
|

Sensory innervation of white adipose tissue

Abstract: The presumption that sensory information does not arise from white adipose tissue was reevaluated using the neuroanatomical tracer, "true blue." Fluorescent cell bodies were observed in dorsal root ganglia of rats after tracer was implanted into inguinal or dorsal subcutaneous fat depots. Sensory information from adipose tissue may play an important role in the regulation of regional and total body fat mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
68
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 0 publications
4
68
1
Order By: Relevance
“…Collectively, we present for the first time the central targets of WAT sensory afferents and demonstrate a condition that stimulates these afferents. Therefore, these data reinforce and greatly extend the seminal finding of the sensory innervation of WAT demonstrated over 20 years ago in a more limited manner when a traditional retrograde tract tracer injected into WAT-labeled DRG pseudounipolar neurons (18).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Collectively, we present for the first time the central targets of WAT sensory afferents and demonstrate a condition that stimulates these afferents. Therefore, these data reinforce and greatly extend the seminal finding of the sensory innervation of WAT demonstrated over 20 years ago in a more limited manner when a traditional retrograde tract tracer injected into WAT-labeled DRG pseudounipolar neurons (18).…”
Section: Discussionsupporting
confidence: 84%
“…Sensory innervation of WAT was shown directly when a conventional retrograde tract tracer was applied to laboratory rat WAT, resulting in labeling of the pseudounipolar (a.k.a. bipolar) neurons of dorsal root ganglia (DRG) (18). In addition, while the present study was in progress, it was reported that injections of the cholera toxin b subunit (CTb) injections into rat retroperitoneal WAT suggest sensory nerve projections to the nucleus gracilis (Gr) of the brainstem (26).…”
mentioning
confidence: 73%
“…It can not be excluded that the effects of neonatal capsaicin-treatment on lipogenesis and plasma non-esterified fatty acid concentrations may result from a direct effect of capsaicin on adipose tissue sensory nerves. Consistent with this, it has been reported that inguinal and dorsal subcutaneous fat depots in rats contain sensory nerve terminals [29] which are sensitive to capsaicin.…”
Section: Discussionsupporting
confidence: 80%
“…The sensory innervation of WAT is suggested by the existence of substance P and calcitonin gene-related peptide, typical marker peptides of primary sensory neurons 29 . Retrograde-tracing experiments also revealed that peripheral pseudounipolar dorsal root ganglion cells innervate WAT 30 . Song et al 31 further showed that afferent nerves in WAT project into many areas of brain, including the hypothalamus.…”
Section: Discussionmentioning
confidence: 89%